A formação docente continuada na Universidade Federal de Uberlândia à luz das competências profissionais - Manzan, Fabiana Pádua de Urzedo (2017)
The contemporary labour world has been going through massive changes that influence the educational field. In this sense, the focus of this research was the professional competences linked to the continuous training of higher education teachers with the aim of guaranteeing improvements in undergraduate education. The main purpose of this study was to identify and analyze how the continuous teacher education in Federal University of Uberlândia (UFU) is configured, using professional skills as a reference. The convergences and divergences between the prevalent competences for teaching in higher education and the formative actions promoted by Teacher Training Committee (DIFDO) of the Federal University of Uberlândia (UFU), under the institutional and legal perspective of UFU’s teachers, were considered. The research was mainly based on the teachings of the following authors: McClelland, McLagan, Zarifian, Le Boterf, Paiva, Cheetam and Chivers, Fleury and Fleury, Perrenoud, Freire, Nóvoa, Zabalza, Cunha, and Imbernón. During this research, the concept of professional competence proposed by Paiva (2007) was emphasised with five dimensions of competences: intellectual, technical-functional, behavioral, ethical and political. The study is a mixed approach research, being qualitative and quantitative, adopting the case study as a research strategy. Regarding the objectives, the study had a descriptive character, and the data sources were: bibliographic research related to the theme and to the documentary research, especially in the archives of DIFDO and Teacher Support Committee (DIADO), and pertinent laws. The results obtained from this study revealed that the institutional-legal vision of the prevalent competences of teaching in higher education rests mainly on the titration and on the intellectual production. There was also a predominance of elements related to the technical- functional competencies, which is consonant with the DIFDO’s work. However, there was some divergence between the real need of UFU’s teachers, which are based on the intellectual production and what is proposed, understanding that it is important to rebuild the formative actions, so that the teachers’ continuous training at UFU can be successful in the development of professional skills.